2001
DOI: 10.1210/jcem.86.9.7867
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Basal Aldosterone to Renin Ratio and of the Renin Stimulation Test by Furosemide and Upright Posture in Screening for Aldosterone-Producing Adenoma in Low Renin Hypertensives

Abstract: An aldosterone-producing adenoma causes surgically correctable hypertension. Screening tests should be assessed for their accuracy and ability to detect aldosterone-producing adenoma in an appropriate population. This study aims to validate the accuracy and efficacy of the basal plasma aldosterone concentration (picomoles per liter) to PRA (nanograms per liter/sec) ratio and of combined stimulation of PRA by the furosemide and upright posture test in screening for aldosterone-producing adenoma in hypertensives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 19 publications
0
21
1
Order By: Relevance
“…For these reasons it has been proposed to improve the accuracy of ARR by increasing the minimum PRA level in the ratio or by requiring a minimum aldosterone level. 5,11,16,18 Following these approaches we have examined different criteria and cutoffs, including those proposed for the supine position 19,20,26 and found that ARR becomes significantly dependent on the ovarian cycle when coupled with either a minimum PRA level of 0.5 ng ml À1 h À1 or a minimum aldosterone level of 15 ng 100 ml À1 . Finally, if one looks only at supine aldosterone levels, the influence of the ovarian cycle is clearly evident using a cutoff of plasma aldosterone415 ng 100 ml À1 , comparable to that considered by Tanabe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons it has been proposed to improve the accuracy of ARR by increasing the minimum PRA level in the ratio or by requiring a minimum aldosterone level. 5,11,16,18 Following these approaches we have examined different criteria and cutoffs, including those proposed for the supine position 19,20,26 and found that ARR becomes significantly dependent on the ovarian cycle when coupled with either a minimum PRA level of 0.5 ng ml À1 h À1 or a minimum aldosterone level of 15 ng 100 ml À1 . Finally, if one looks only at supine aldosterone levels, the influence of the ovarian cycle is clearly evident using a cutoff of plasma aldosterone415 ng 100 ml À1 , comparable to that considered by Tanabe.…”
Section: Discussionmentioning
confidence: 99%
“…19 Some limitations of the study should be mentioned. Firstly, although the diagnostic work-up for primary aldosteronism is still controversial, 11,12,16,17,26 according to the prevailing experts opinion, [11][12][13] the determination of PRA and aldosterone represents the first screening test, that should be followed by a confirmatory test (for example, fludrocortisone test, captopril test or saline infusion) that investigates the autonomous aldosterone secretion. Therefore, as no definite diagnosis of primary aldosteronism was made in our patients, our conclusions do not allow to establish the relevance of the ovarian cycle on the overall diagnostic process for the disease, which requires further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Even among African-American subjects, where the ARR is less sensitive than in white subjects (75 vs 80%), it still had a high negative predictive value (92 vs 94%) 23 suggesting that while the ARR is valid as a screening test for primary hyperaldosteronism in African American and white patients on stable antihypertensive treatments, there will be significant false-positivity and a high ratio while suggestive of primary hyperaldosteronism, must be confirmed (Table 3). 43 Upright PAC 4166 pmol/l and PRA o1.0 mg/l/h at 10 am on day 4, coupled with normal plasma potassium levels, cortisol at 1000 hours no greater than at 0700 hours on day 4, and urinary sodium 43 mmol/kg/day on day 3 Intravenous saline load 6,10,53,55,56 Intravenous infusion of 2 l of 0.9% sodium chloride solution over 4 h (500 ml/h) Plasma aldosterone after infusion 4236 pmol/l (140-235 pmol/l grey zone) Oral sodium load 10,20,22 Oral sodium chloride supplementation (300 mmol of sodium per day for 3 days) and potassium supplementation (if required) Urinary aldosterone on the third day 439 nmol (412 mg) in 24 h, and urinary sodium 4200 mmol in 24 h ARR after captopril 31,32 A second determination of the ARR 2 h after oral 25 mg captopril Post-captopril ARR 412 (ng/dl)/(mg/l/h) AND PA 4 330 pmol/l Renin stimulation test 44,47,48 Furosemide 40 mg orally every 8 h the proceeding day and 0800 hours the next day followed by 2 h ambulation and sampling of renin. OR i.v.…”
Section: Confirmatory Testingmentioning
confidence: 99%
“…[44][45][46][47][48] This is done using furosemide 40 mg given orally eight hourly the preceding day and in the morning followed after 2 h of upright ambulation by blood sampling for PRA at 0800 hours. After such a hypovolaemic stimulation, PRA remains suppressed.…”
Section: Confirmatory Testingmentioning
confidence: 99%